Evaluation and comparison of the antifertility potential activity and adverse effects of Trigonella foenum-graecum seeds and combined oral contraceptive pills in female rats. - Hilles, Ayah Rebhi; Allow, Ahmed Kaid Naji; Mahmood, Syed (medip Academy, 2016)
Antifertility agents are one of the most common medication used in this modern era. In this research we used herbal plant Trigonella foenum-graecum (fenugreek) seeds to study the antifertility activity of Fenugreek Seeds allowed aqueous (FSA) extract in female rats compared with marketed combined oral contraceptive pills (COCPs) by evaluating Follicle Stimulating Hormone (FSH) level and to detect the adverse effects by determining the uterine weight, implantation rate, endometrial thickness, endometrial gland density and observing the histological uterine tissues. Methods: Twenty four female Sprague Dawley strain rats of 8 weeks old were divided into four groups (A, B, C and D). Animals in Group A (positive control group) were not given any treatment and they were allowed to mate to become pregnant. Group B (negative control group) were not given any treatment as only female rats were kept. Group C (treated group) they were administered orally with 0.05 mg/kg body weight of COCPs for 15 days. Group D (treated group) they were administered orally with 750 mg/kg body weight of FSA extract for 15 days. The blood samples were taken after the both treatment on the proestrous phase to evaluate FSH level. In group A, C and D, 3 male rats of Spargue Dawley strain were also kept to do the mating process. Results: Administration of 0.05mg/kg of COCPs led to decrease the serum FSH concentration to 71.56 ng/ml while 750 mg/kg FSA extract led to decrease it to 25.62 ng/ml, which shows that FSA extract is effective almost three times more than COCPs at higher dose. The uterine weight in the FSA extract treated group was normal, while the COCPs treated group was insignificantly high. The implantation rate was zero in all groups except the positive control group. The endometrial thickness in the FSA extract treated group was normal while in the COCPs increased. The endometrial gland density was normal in FSA extract treated group, while it decrease in COCPs treated group which a remarkable sign of endometrial atrophy. Histological endometrial tissues were normal in FSA extract treated group while COCPs treated group showed abnormal deciduiod cells (decidual like cells). Conclusions: Administration of FSA extract decreased FSH concentration to almost three times more than OCCPs which show the high effectiveness of FSA extract more than marketed COCPs, not only that but it also showed no adverse effects in the uterine opposite with COCPs which guide us to alternative natural and safe contraceptive method.